1989
DOI: 10.1002/chin.198917024
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Electrochemical, Ellipsometric, and Surface Science Investigation of the PtRu Bulk Alloy Surface.

Abstract: Utilizing in situ ellipsometric measurements coupled with electrochemical measurements of bulk PtRu in sulfuric acidic solution at 20 °C show that a chemisorbed oxygen species is formed on the alloy surface at potentials as low as +0.25 V vs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1993
1993
1993
1993

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…As the ruthenium surface concentration is reduced to «30 atomic % (PtRu-5, Figure 3c) and then to «10 atomic % (PtRu-3, Figure 3d), the "doublelayer" currents decrease and the "hydrogen region" begins to resemble the features of pure platinum. The major change in the voltammetric response due to Ru in the Pt surface is the increasing ratio of the "double-layer" currents over the currents in the "hydrogen region" as the ruthenium surface concentration is increased, indicating the adsorption of oxygen-like species at progressively more negative potentials, as was noted also by Ticanelli et al 26 This plays an important role in the electrooxidation of methanol, which we will address in the following. 3.2.2. Voltammetry in the Presence of Methanol.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…As the ruthenium surface concentration is reduced to «30 atomic % (PtRu-5, Figure 3c) and then to «10 atomic % (PtRu-3, Figure 3d), the "doublelayer" currents decrease and the "hydrogen region" begins to resemble the features of pure platinum. The major change in the voltammetric response due to Ru in the Pt surface is the increasing ratio of the "double-layer" currents over the currents in the "hydrogen region" as the ruthenium surface concentration is increased, indicating the adsorption of oxygen-like species at progressively more negative potentials, as was noted also by Ticanelli et al 26 This plays an important role in the electrooxidation of methanol, which we will address in the following. 3.2.2. Voltammetry in the Presence of Methanol.…”
Section: Resultssupporting
confidence: 52%
“…The overlap of hydrogen desorption and oxide formation regions on Ru electrodes which seems to be indicated in Figure 3a was investigated via "chloride blocking" experiments and electroreflectance experiments by Hadzi-Jordanov ef a/.15 as well as via ellipsometric measurements by Ticanelli and co-workers. 26 Both groups concluded that the onset of the adsorption oxygen-like species would occur at potentials as low as 0.2 V, such that it coincides with the desorption of hydrogen. Therefore, they concluded that electrochemical surface areas on ruthenium electrodes could not be assessed by coulometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation